2015
DOI: 10.1080/13691058.2014.989265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of young people's sexual aggression perpetration and victimisation in 10 European countries: a multi-level analysis

Abstract: Data are presented on young people's sexual victimisation and perpetration from 10 European countries (Austria, Belgium, Cyprus, Greece, Lithuania, the Netherlands, Poland, Portugal, Slovakia and Spain) using a shared measurement tool (N = 3480 participants, aged between 18 and 27 years). Between 19.7 and 52.2% of female and between 10.1 and 55.8% of male respondents reported having experienced at least one incident of sexual victimisation since the age of consent. In two countries, victimisation rates were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

30
172
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(210 citation statements)
references
References 23 publications
30
172
2
6
Order By: Relevance
“…About 12% of men and 7% of women reported committing a sexually aggressive act at least once since the age of 15. For both genders, the rates of sexual aggression perpetration were lower than the rates of sexual victimization, which is consistent with previous findings (Kolivas & Gross, 2007;Koss, 1993;Krahé & Berger, 2013;Krahé et al, 2015). Other Polish studies obtained similar overall rates of sexual victimization, such as 36.4% for men and 31.3% for women (Izdebski, 2012), 32% for men and 35.4% for women (Łukaszek, 2013) as well as of sexual aggression perpetration, such as 7.3% for men and 6.3% for women (Krahé et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…About 12% of men and 7% of women reported committing a sexually aggressive act at least once since the age of 15. For both genders, the rates of sexual aggression perpetration were lower than the rates of sexual victimization, which is consistent with previous findings (Kolivas & Gross, 2007;Koss, 1993;Krahé & Berger, 2013;Krahé et al, 2015). Other Polish studies obtained similar overall rates of sexual victimization, such as 36.4% for men and 31.3% for women (Izdebski, 2012), 32% for men and 35.4% for women (Łukaszek, 2013) as well as of sexual aggression perpetration, such as 7.3% for men and 6.3% for women (Krahé et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Sexual aggression was defined in the current study as any type of behavior that aims at making another person engage in sexual activity against her or his will (Krahé, 2013 (Czapska, Klosa, Lesińska, & Okrasa, 2012;Gruszczyńska, 2007), and no study addressed only men as victims. No more than 4 studies investigated the perpetration of sexual aggression, all including both gender groups (Doroszewicz & Forbes, 2008;Izdebski, 2012;Krahé et al, 2015;Łukaszek, 2013).…”
mentioning
confidence: 98%
“…More than 50% of the participants were victims of several aggressors, most of whom were men, although 19% were subjected to assaults by aggressors of both sexes. This data is consistent with previous studies conducted in other countries showing that women are more often impacted, endure longer lasting violence and are predominantly victims of male perpetrators [18][19][20][21]. The survey data also confirmed that sexual violence starts most often during childhood and adolescence [22,23].…”
Section: Discussionsupporting
confidence: 82%
“…A recent study from 10 European countries reports that between 2.6% and 14.8% of women admit to having engaged in sexual aggression (Krahé et al, 2015). A German study among 2149 university students found that 7.9% of women report perpetration of sexual coercion, with 4.3% using verbal pressure, 2.6% using alcohol-related strategies and 2.3% of women admitted using force (Krahé & Berger, 2013).…”
Section: Coercive Strategiesmentioning
confidence: 99%
“…Different types of coercive strategies can be distinguished, for example: the use of threat or physical force, the exploitation of the other person's inability to resist the unwanted advances and the use of verbal pressure (Krahé et al, 2015). In a study among 656 US college students, 26% of women and 40% of men reported having used coercive strategies (Struckman-Johnson, Struckman-Johnson, & Anderson, 2003).…”
Section: Coercive Strategiesmentioning
confidence: 99%